MAREBAT TRADITION IN TOBANESE ETHNIC: A STUDY OF LOCAL WISDOM - Herlina, Herlina; Sitohang, Nerlika; Purba, Asriaty R (Kompetensi : Jurnal Pendidikan dan Humaniora Fakultas Keguruan dan Ilmu Pendidikan UNIBA, 2023)
This scientific article is entitled “Marebat Tradition in Tobanese Ethnic: A Study of Local Wisdom. The marebat tradition is a tradition of bringing parumaen (daughter-in-law) to the village or the hula-hula house. The Marebat tradition is carried out within one to two weeks after the wedding and this tradition is carried out at the house of the parboru (The bride's parents). This article discusses two core issues as a discussion of the formulation of the problem, namely the stages of the marebat tradition in the Tobanese ethnicity and describes the types of local wisdom found in the marebat tradition in the Tobanese ethnicity. This article uses a qualitative descriptive research method. This study used the theory of oral tradition by Robert Sibarani (2015). Oral tradition is a traditional activity of a community that is passed down from generation to generation with oral media from one generation to another, whether the tradition is in the form of oral words (verbal) or non-verbal oral traditions. verbal (non-verbal)”. Sources of data and information about the marebat tradition were obtained by the authors from primary data sources which were the results of interviews. Based on the results of the research, the authors found that there are nine stages in the marebat tradition, and in the stages of the marebat tradition there is local wisdom derived from the core local wisdom of peace and prosperity, namely politeness, cooperation, caring and compassion, perseverance, discipline, commitment, caring. environment, respect, honesty, health, preservation and cultural creativity, gratitude, social solidarity, harmony and conflict resolution, gender management, control, love of culture, independence, and trust.